SOCIAL IDEAL IDENTIFICATIONS IN ORIENTAL AND WESTERN PHILOSOPHY - Agzamkhodzhaeva, S.; Abdurashidovna, Mukhitdinova Firyuza; Vakhabovna, Akhmetzhanova Mukaddas (International Journal of Psychosocial Rehabilitation, 2020)
This paper was analaysed social ideal identifications in oriental and western philosophy. Therefore, social idea of the oriental and western philosophy. In conclusion, research has been concluded with the features of the identifications of oriental and western philosophy.